Konstruksi Media Online Terhadap Kebijakan Pembatasan Sosial Berskala Besar (PSBB) COVID-19 DKI Jakarta - Denune Gentastilar Wangsemukti; Nasrullah Nasrullah (Jurnal Spektrum Komunikasi, 2021)
The Large-Scale Social Restriction Policy (PSBB) is decided by the government to reduce the number of the spread of the COVID-19 pandemic in the DKI Jakarta Province. This study aims to describe how online media constructs this policy through media framing. The two media studied were detik.com and narasi.tv. Framing analysis uses the Robert N Etman concept to determine problem identification, casual interpretation, treatment recommendation, and moral evaluation. The results showed that the two media construct PSBB differently. Detik.com sees PSBB as a policy formed as a result of community disobedience to health protocols. This media constructs society and COVID-19 as actors causing policy. Meanwhile, Narasi.tv sees the PSBB as a form of government flight from responsible. This media tends to blame government for the high number of COVID-19 cases in DKI Jakarta.